Exploring Innovative Teaching Modes for Programmable Logic Controllers under the “New Engineering” Background - Liu, Jing (Journal of Research in Vocational Education, 2025)
Under the “New Engineering” initiative, which emphasizes interdisciplinary integration, industry-academia collaboration, and innovative talent cultivation, this study explores a reformed teaching model for Programmable Logic Controller (PLC) courses. By integrating project-based learning, deep industry-academia collaboration, and a BOPPPS (Bridge-In, Objective, Pre-assessment, Participatory Learning, Post-assessment, Summary) evaluation system, this research addresses the disconnection between theoretical instruction and practical application in traditional PLC education. The outcomes demonstrate significant improvements in students’ practical skills, innovative thinking, and adaptability to industrial demands. This model not only enhances the quality of applied engineering education but also provides a replicable framework for similar technical courses. Quantitative data, qualitative feedback, and longitudinal comparisons highlight the effectiveness of the proposed approach, positioning it as a benchmark for future curriculum reforms in technical disciplines.